Nutrient Composition of Red and White Cultivars of Dried Moringa oleifera Leaves from Probolinggo, Indonesia - Mudita, Dhaniar; Harijono, Harijono; Widjajanto, Edi (Direktorat Riset dan Pengabdian Masyarakat, Universitas Brawijaya, 2021)
Moringa oleifera is a popular plant for combating malnutrition that grows well and is commonly consumed by Indonesian as a vegetable, but local varieties' nutrient composition never was studied before. Methods: Proximate, amino acids, minerals, vitamin C, and total phenolic composition of red and white cultivars of Moringa oleifera leaves from Probolinggo were determined on a dry weight basis based on AOAC methods. Results: Crude protein and fat were higher in white cultivar (35.36%, 6.25%). Total Amino Acid in both cultivars (83.06 g/100g for red and 82.86g/100g for white) were higher than in previous studies. Total Essential Amino Acid (TEAA) percentage of both of the cultivars was 46-49% and met the ideal protein needs of children (26%) and adults (11%). Iron, Zinc, Copper, Calcium, and Manganese was higher in white cultivar (36.21±0.08 mg/kg, 16.32±0.02%, 6.76±0.08mg/kg, 1.56±0.00 mg/kg, 7.11±0.00 mg/kg), while Magnesium, Potassium, Sodium, Phosphorus was higher in red cultivar (0.61±0.00%, 0.89±0.00%, 0.65±0.00%, 0.99±0.00). The content of vitamin C and total phenols was higher in the red cultivar (4162.8mg/kg and 239.8mg/kg). Conclusions: The red cultivar were best in 10/22 parameters (45%), white cultivar was best in 14/22 (55%). Those characteristics can contribute significantly to the nutrient requirements for protein and energy malnutrition treatment.